AI USE AND THE FULFILLMENT OF BASIC PSYCHOLOGICAL NEEDS IN PROJECT-BASED LEARNING: A SELF-DETERMINATION THEORY PERSPECTIVE IN SECONDARY EDUCATION - Amalia Rahmah; Dimas Aji Nugroho; Rusmanto Rusmanto (Universitas Tribhuwana Tunggadewi, 2026)
The integration of Artificial Intelligence (AI) into education has grown rapidly, yet its psychological effects on students, particularly in Project-Based Learning (PBL), remain insufficiently understood. Grounded in Self-Determination Theory (SDT), this study examines the relationship between AI use and students’ basic psychological needs, namely autonomy, competence, and relatedness. A quantitative cross-sectional survey was conducted with 96 junior high school students aged 12–15 years at a nature-based PBL school in Depok, Indonesia. Data were analyzed using simple linear regression. The results showed that AI use was positively and significantly associated with autonomy (B = 0.343, ? = 0.352, p .001), but not with competence (p = .500) or relatedness (p = .993). However, the autonomy finding should be considered preliminary because the reliability of the autonomy instrument was below the recommended threshold, indicating the need for replication using a more reliable measure. These findings suggest that AI’s contribution to students’ basic psychological needs is selective rather than uniform, with AI primarily supporting autonomy while showing no significant relationship with competence or relatedness in a nature-based PBL environment.